Evaluasi Potensi Airtanah dengan Metode Geolistrik di Desa Lipukasi Kabupaten Barru - Darwis, Muh (LaGeografia, 2020)
The groundwater research area is included in the Lipempuan Village area. This research was conducted using the geoelectric method, using the Schlumberger linear symmetry configuration. Measurement of the type of resistivity was carried out at 12 geoelectric points. The research method uses qualitative methods. The measurement results show a cross section of resistors of types BR33-BR34-BR35-BR36-BR40-BR42 in general shows a layer of fresh shallow groundwater at depths (1.5 - 10) m, low productive productive groundwater at depths (10 - 75) m and local shows brackish-saltwater groundwater, productive groundwater is fresh at a depth (75 - 100) m. Sectional cross sections of types BR37-BR38-BR39-BR41-BR43-BR44 generally show a layer of fresh shallow groundwater at depths (1.5 - 10) m, low productive productive groundwater at depths (10 - 50) m, productive groundwater is fresh at depth (50 - 150) m. Underground water development can be done by drilling. Underground water drilling based on the results of the analysis of resistivity data is recommended at geoelectric point estimates: BR40, BR43, BR37, BR44.